Implementation of treatment recommendations for chronic hepatitis B in patients attending specialized hospital care in Denmark – a region wide study. (2nd July 2020) - Bollerup, Signe; Hallager, Sofie; Baek, Ole; Krarup, Henrik; Madsen, Lone Galmstrup; Thielsen, Peter; Balslev, Ulla; Mens, Helene; Barfod, Toke; Rye Clausen, Mette; Hobolth, Lise; Gerstoft, Jan; et al.
Abstract: Objective: To evaluate implementation of national guideline recommendations on treatment initiation for chronic hepatitis B (CHB) in Denmark. Methods: Using DANHEP, a nationwide cohort of chronic hepatitis B and C patients attending specialized hospital care in Denmark, we performed a descriptive cohort study from January 2002 through December 2017. We identified patients with CHB in 3 of 5 Danish regions, with at least two hospital/outpatient clinic visits during the study period. Results: We identified 990 CHB patients who remained untreated throughout the study period, and 265 who initiated treatment. At their last visit 952/990 (96%, 95% CI 95–97) untreated patients did not meet current national criteria for treatment initiation while 198/265 (75%, 95% CI 69–80) who initiated treatment met the national criteria. Overall, 198/236 (84%, 95% CI 79–88) who met national treatment criteria, initiated treatment. Conclusion: The majority of CHB patients received care in line with national guideline recommendations for treatment initiation. We found that only few patients eligible for treatment remained untreated. However, a fourth of patients who received treatment were not eligible according to national guidelines.